Cars : a read-aloud storybook - Marsoli, Lisa.; Disney Storybook Artists; Pixar (Firm) (New York : Random House, 2006)
Based upon the Disney film, Lightning McQueen, the rookie hot-shot race car, is screaming his way down the track on his way to winning the Piston Cup, but he gets stuck in a slow little town called Radiator Springs.
3.0
K-3
K-3
Keywords: Automobile racing -- Juvenile fiction; Automobile racing -- Fiction; Adventure and adventurers -- Fiction; Automobile racing -- Fiction; Adventure fiction